2011
DOI: 10.1073/pnas.1015633108
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic disruption of sleep continuity impairs memory consolidation

Abstract: Memory consolidation has been proposed as a function of sleep. However, sleep is a complex phenomenon characterized by several features including duration, intensity, and continuity. Sleep continuity is disrupted in different neurological and psychiatric conditions, many of which are accompanied by memory deficits. This finding has raised the question of whether the continuity of sleep is important for memory consolidation. However, current techniques used in sleep research cannot manipulate a single sleep fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
132
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(143 citation statements)
references
References 39 publications
8
132
1
2
Order By: Relevance
“…Using an optogenetic approach to wake up mice by activating orexin/hypocretin neurons, the laboratory of de Lecea recently found that the consolidation of memories for object identity is attenuated by sleep fragmentation during the first 4 h after training (Rolls et al 2011). When the average duration of sleep episodes was maintained at around 70 % of normal, the memory for the object identity was unaffected.…”
Section: Sleep and Fear Memoriesmentioning
confidence: 98%
“…Using an optogenetic approach to wake up mice by activating orexin/hypocretin neurons, the laboratory of de Lecea recently found that the consolidation of memories for object identity is attenuated by sleep fragmentation during the first 4 h after training (Rolls et al 2011). When the average duration of sleep episodes was maintained at around 70 % of normal, the memory for the object identity was unaffected.…”
Section: Sleep and Fear Memoriesmentioning
confidence: 98%
“…Indeed, even when sleeping in flight, sleep was more fragmented and less deep than sleep on land. In contrast with frigatebirds, in animals ranging from insects [92] to humans [93], far shorter periods of sleep restriction and fragmentation [94] have profound adverse effects on their ability to maintain wakefulness and interact adaptively with the environment. People fall asleep while driving a car after losing just a few hours of sleep, even when aware of the dangers and trying to keep themselves awake.…”
Section: General Implicationsmentioning
confidence: 99%
“…Subsequently, they showed that optic stimulation (once every 60 s) caused frequent, brief arousals, without altering the total sleep time or architecture. After 4 hours of this stimulus, mice exhibited deficits in memory consolidation (68).…”
Section: Ihmentioning
confidence: 99%